Heart health for South Asians: improved cardiovascular risk factors with a culturally tailored health education program - Paniz Vafaei; Chi-Mei Liu; Hank Davis; Priyal Patel; Uma Vadlakonda; Seema Pursnani (BMC Public Health, 2023)
Abstract Background/Aim The Kaiser Permanente (KP) Northern California Heart Health for South Asians (HHSA) Program is a two-hour educational class that provides culturally relevant lifestyle and dietary recommendations to South Asian (SA) patients, in an effort to reduce their known disproportionate burden of cardiovascular (CV) disease. We evaluated the impact of the HHSA Program on CV risk factors and major adverse CV events (MACE). Methods A retrospective cohort study identified 1517 participants of SA descent, ≥ 18 years old from 2006 to 2019. We evaluated the change in risk factors with program attendance (median follow up of 6.9 years) for systolic blood pressure (SBP), diastolic blood pressure (DBP), triglycerides (TG), LDL, HDL, BMI, and HbA1c. We also performed a propensity matched analysis to evaluate differences in MACE including stroke, myocardial infarction (MI), coronary revascularization, and all-cause mortality. Results There were significant improvements in DBP, TG, LDL-c, HDL-c, BMI, and HbA1c at one year follow up and sustained improvements in DBP (-1.01mmHg, p = 0.01), TG (-13.74 mg/dL, p = 0.0001), LDL-c (-8.43 mg/dL, p = < 0.0001), and HDL-c (3.16 mg/dL, p = < 0.0001) levels at the end of follow up. In the propensity matched analysis, there was a significant reduction in revascularization (OR 0.33, 95% CI 0.14–0.78, p = 0.011) and mortality (OR 0.41, 95% CI 0.22–0.79, p = 0.008), and a trend towards reduction in stroke. Conclusions Our study demonstrates the efficacy of a culturally tailored SA health education program in improving CV risk factors and reducing MACE. The program highlights the importance and value of providing culturally tailored health education in primary CV disease prevention.